Development of a Project-Based Learning Management System to Improve VLAN Configuration Competence (Case Study of Class XI TKJ Students at SMKN 1 Surabaya) - Galang Satria Pratama Putra; Ekohariadi Ekohariadi; Cahyo Febri Wijaksono (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aims to develop a Moodle-based Learning Management System (LMS) integrated with a Project-Based Learning (PjBL) approach and to examine its effectiveness in improving Virtual Local Area Network (VLAN) configuration competencies among eleventh-grade students of the Computer and Network Engineering (CNE) program at SMKN 1 Surabaya. Method: The research employed a Research and Development (R&D) method using the ADDIE model. The subjects were an experimental and a control class. Data were collected through expert validation, cognitive tests, and psychomotor performance assessments. Data analysis was conducted using the Mann–Whitney U test and the independent-samples t-test based on the data distribution. Results: The developed LMS demonstrated very high feasibility, with a media validation score of 93.3%. Statistical analysis revealed significant differences in both cognitive and psychomotor competencies between the experimental and control groups (p < 0.05). These findings indicate that integrating a Moodle-based LMS with the PjBL approach effectively enhances students' VLAN configuration competencies in vocational education. Novelty: The novelty of this study lies in the explicit integration of Project-Based Learning syntax into the design and functionality of a Moodle-based LMS for VLAN configuration practice, enabling a balanced development of theoretical understanding and psychomotor skills within a vocational, project-oriented learning context.